Climatic variables and reported cases of dengue in the city of Uberaba, Minas Gerais, Brazil - Almeida, Fabrício Pelizer; Ribeiro, Flávia Alice Borges Soares (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The dynamics of the climatic elements of a given region, intervenes in the socio-environmental relations constituted, including the aspects of environmental health, prevalence of vectors transmitting diseases and the local epidemiological scenario. The objective of this study was to describe the capacity of impulse-response transmission between the historical records of climatic variables and the data of reported cases of dengue fever in the city of Uberaba, Minas Gerais, using a vector autoregressive (VAR) model. Monthly average climatic secondary data and reported cases of dengue were tabulated from January 2009 to December 2016 for the municipality. An autoregressive vector (VAR) model of the logarithmic historical series was developed, obtaining response graphs in the number of reported cases of dengue (dependent variable) due to the impulses in the climatic components (independent variables). The results showed that the 1% increase in temperature corresponds to a 0.45% increase in the number of dengue cases in the following month, reducing the effect from the 3rd month. The increase in precipitation impacts up to 0.15% in the reported cases of dengue in the following month, while the increase in the relative air humidity index negatively impacts the dependent variable. The historical series of reported cases of dengue is dependent on impulses from the variable itself (68%) and about 20% of the variations in average monthly temperature. Given the adaptability of disease vectors to climatic variations, municipal epidemiological control strategies should include the planning, monitoring and management of local climatic indicators due to socio-environmental vulnerability.